Oxygen‐Dependent Photocatalytic Water Reduction with a Ruthenium(imidazolium) Chromophore and a Cobaloxime Catalyst. Issue 24 (2nd May 2016) - Petermann, Lydia; Staehle, Robert; Pfeifer, Maxim; Reichardt, Christian; Sorsche, Dieter; Wächtler, Maria; Popp, Jürgen; Dietzek, Benjamin; Rau, Sven
Abstract: Detailed investigations of a photocatalytic system capable of producing hydrogen under pre‐catalytic aerobic conditions are reported. This system consists of the NHC precursor chromophore [Ru(tbbpy)2 (RR′ip)][PF6 ]3 (abbreviated as Ru(RR′ip)[PF6 ]3 ; tbbpy=4, 4′‐di‐ tert ‐butyl‐2, 2′‐bipyridine, RR′ip=1, 3‐disubstituted‐1 H ‐imidazo[4, 5‐ f ][1, 10]phenanthrolinium), the reduction catalyst Co(dmgH)2 (dmgH=dimethylglyoximato), and the electron donor ascorbic acid (AA). Screening studies with respect to solvent, cobaloxime catalyst, electron donor, pH, and concentrations of the individual components yielded optimized photocatalytic conditions. The system shows high activity based on Ru, with turnover numbers up to 2000 under oxygen‐free and pre‐catalytic aerobic conditions. The turnover frequency in the latter case was even higher than that for the oxygen‐free catalyst system. The Ru complexes show high photostability and their first excited state is primarily located on the RR′ip ligand. X‐ray crystallographic analysis of the rigid cyclophane‐type ligand dd(ip)2 (Br)2 (dd(ip)2 =1, 1′, 3, 3′‐bis(2, 3, 5, 6‐tetramethyl‐1, 4‐phenylene)bis(methylene)bis(1 H ‐imidazo[4, 5‐ f ][1, 10]phenanthrolinium)) and the catalytic activity of its Ru complex [(tbbpy)2 Ru2 (μ‐dd(ip)2 )][PF6 ]6 (abbreviated as Ru2 (dd(ip)2 )[PF6 ]6 ) suggest an intermolecular catalytic cycle. Abstract : Oxygen‐dependent photocatalytic water reduction : A detailed investigation of a photocatalytic system capable of producing remarkably high turnover numbers under pre‐catalytic aerobic conditions is reported. This system consists of the NHC precursor compound [Ru(RR′ip)][PF6 ]3 as the chromophore, [Co(dmgH)2 ] as the reduction catalyst, and ascorbic acid as the electron donor (see graphic).